C7 slope and its association with serum lipid levels and Modic changes in patients with cervical spondylotic myelopathy - Lv B; Xu T; Wan B; Ding H; Yao X; Chen J; Ji P; Zhao Y; Luo Y; Zhou Z; Yang S; Jiang Q; et al. (Journal of Pain Research, 2019)
Bin Lv1,*, Tao Xu2,*, Bowen Wan2,*, Hua Ding,1 Xiang Yao,1 Jian Chen,2 Peng Ji,1 Yilei Zhao,1 Yongjun Luo,2 Zhimin Zhou,2 Shengquan Yang,3 Qinyi Jiang,1 Jishan Yuan,1 Guoyong Yin21Department of Orthopedics, The Affiliated People’s Hospital of Jiangsu University, Zhenjiang, Jiangsu Province 212002, People’s Republic of China; 2Department of Orthopedics, The First Affiliated Hospital with Nanjing Medical University, Nanjing, Jiangsu Province 210029, People’s Republic of China; 3Department of Orthopedics, Yancheng No.1 People’s Hospital, Yancheng, Jiangsu Province 224000, People’s Republic of China*These authors contributed equally to this work Background: Several studies have substituted the T1 slope (T1S) with the C7 slope (C7S) because the C7 endplate is clearer on radiographs. Further, abnormal serum lipid levels have been proven to be related with the development of disc degeneration. The aim of this study was to explore the relationship between C7S, serum lipid levels, cervical parameters related to cervical sagittal balance and Modic changes (MCs) in patients with multisegment cervical spondylotic myelopathy (CSM).Methods: Between January 2014 and January 2017, 75 patients with multisegment CSM were enrolled in our retrospective study. Gender, age, history of smoking status and alcohol consumption, and laboratory test data were recorded. The cervical sagittal balance parameters C7S, T1S, cervical lordosis (CL), neck tilt (NT), thoracic inlet angle (TIA), C2–C7 sagittal vertical axis (SVA), and T1S-CL were analyzed with Spearman correlation tests and multiple linear regression analysis. We diagnosed MCs through computed tomography or magnetic resonance imaging of the cervical spine. Patients were divided into four subgroups according to the presence or absence of MCs and their C7S values.Results: 75 patients were included in our study. Age, gender, C7S, and T1S were significantly different between the two groups. However, there was no statistical difference with regard to smoking status, alcohol consumption, lipoprotein(a), high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, albumin, globulin, triglycerides, total cholesterol, Ca,2+ CL, T1S, TIA, NT, and T1S−CL. The correlation between HDL-C, LDL-C, ALB, GLB, Ca,2+ C7S, T1S, MCs, NT, TIA, and C2–C7 SVA was statistically significant.Conclusion: Significant correlations were observed between MCs and TG (as well as other preoperative sagittal parameters), which may accelerate the development of degeneration of the cervical spine. Therefore, alcohol consumption, TG, and sagittal parameters, such as C7S, and T1S could be a promising candidate for the assessment of cervical sagittal balance and predicting neck pain.Keywords: C7 slope, Modic change, serum lipid, cervical myelopathy, neck pain, cervical sagittal alignment